2001
DOI: 10.1021/tx000264z
|View full text |Cite
|
Sign up to set email alerts
|

Monomethylarsonous Acid (MMAIII) and Arsenite:  LD50 in Hamsters and In Vitro Inhibition of Pyruvate Dehydrogenase

Abstract: Monomethylarsonous acid (MMA(III)), a metabolite of inorganic arsenic, has received very little attention from investigators of arsenic metabolism in humans. MMA(III), like sodium arsenite, contains arsenic in the +3 oxidation state. Although we have previously demonstrated that it is more toxic than arsenite in cultured Chang human hepatocytes, there are no data showing in vivo toxicity of MMA(III). When MMA(III) or sodium arsenite was administered intraperitoneally to hamsters, the LD(50)s were 29.3 and 112.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
199
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(208 citation statements)
references
References 29 publications
7
199
0
2
Order By: Relevance
“…MAs(III) is more toxic than inorganic As(III) in Chang human hepatocytes (15) and hamsters (16). We showed that it is more toxic in Escherichia coli cells as well (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…MAs(III) is more toxic than inorganic As(III) in Chang human hepatocytes (15) and hamsters (16). We showed that it is more toxic in Escherichia coli cells as well (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Notably, DMAs III inhibited GLUT4 translocation in insulin-activated adipocytes by a mechanism independent of PKB/Akt phosphorylation. Results from other laboratories suggest that metabolites of iAs may also interfere with glucose metabolism by inhibiting α-ketoglutarate dehydrogenase or pyruvate dehydrogenase (Boquist et al, 1988;Petrick et al, 2001), two rate limiting enzymes involved in the oxidative metabolism of carbohydrates. However, it is unclear whether concentrations of iAs metabolites in tissues of chronically exposed individuals can reach levels necessary for inhibition of these enzymes.…”
Section: Laboratory Studies Of the Effects Of As On Glucose Metabolismmentioning
confidence: 99%
“…Human metabolism of iAs involves the reduction of As(V) to As(III) and the oxidative methylation of As(III)-species that yields methylated arsenicals containing either As(III) or As(V) [1][2][3]. Toxicities of tri-and pentavalent iAs and methylated arsenicals differ significantly [4][5][6]. Therefore, developing methods for the oxidation state specific speciation analysis of As in biological matrices has become a key issue for As toxicology and analytical chemistry.…”
Section: Introductionmentioning
confidence: 99%